Operation status, quality, and premature birth information in obstetrics and gynecology facility websites in Korea: an evaluation study. - Sun-Hee Kim (Women's Health Nursing, 2025)
Purpose: This study aimed to identify the operational status and evaluate the quality of websites run by obstetrics and gynecology medical facilities in Korea, as well as to examine the information provided about premature birth. Methods: Data were collected in April 2022 using the Health Insurance Review and Assessment Service website. A list of tertiary hospitals, general hospitals, hospital (primary-level institutions with =30 beds), and midwifery centers, along with their website addresses, was obtained. A total of 566 websites were analyzed. Information on premature birth was retrieved using integrated search functions on medical facility websites. Text- and video-based content related to premature birth was collected and analyzed using NVivo software (Lumivero). Results: Of 614 obstetrics and gynecology medical facilities, 566 (92.2%) operated websites and 166 (29.3%) had an integrated search function. Premature birth-related information was overwhelmingly text-based (98.7%). The information provided primarily concerned primary prevention. The mean (standard deviation) quality scores of the websites were as follows: purposefulness 4.00 (0.00), credibility 3.58 (0.25), interactivity 3.37 (0.93), currency 3.90 (0.27), ease of use 3.75 (0.18), functionality 4.00 (0.03), design 3.65 (0.38), and confidentiality 3.98 (0.24). Conclusion: The study revealed disparities in website operation across medical institution classifications, limitations in the format of premature birth information, imbalances in content, and gaps in website quality. Future efforts should focus on diversifying both the format and scope of premature birth information while improving website quality across all levels of facilities, including general hospitals and midwifery centers.